Efficacy and safety of sodium-glucose cotransporter 2 (SGLT2) inhibitors in patients with acute heart failure: a systematic review and meta-analysis - Hou, Jingjin; Ren, Li; Hou, Qingbin; Jia, Xiaodong; Mei, Zhu; Xu, Jiaxin; Yang, Zheming; Li, Yiming; Yan, Chenghui (Frontiers in Cardiovascular Medicine, 2024)
The effectiveness and safety of a novel class of hypoglycemic medications known as sodium-glucose cotransporter 2 (SGLT2) inhibitors have not been completely established in relation to acute heart failure (AHF). Consequently, we sought to compare the prognostic and safety outcomes of patients administered SGLT2 inhibitors for the treatment of AHF.Methods: An extensive search of the Web of Science, PubMed, and EMBASE was conducted for randomized controlled trials and observational studies that have evaluated the use of SGLT2 inhibitors in AHF from the inception of these drugs to the present. We compiled data related to cardiovascular safety and prognosis. Aggregated risk ratios (RR), mean differences (MD), or standardized mean differences (SMD)were generated for all outcomes, with 95% confidence intervals (CIs), to evaluate the predictive significance of SGLT2 inhibitors in patients with AHF.We identified 4053 patients from 13 studies. Patients experienced a substantial reduction in all-cause mortality (RR = 0.82, 95% CI: 0.70 -0.96, P = 0.01), readmission rates (RR = 0.85, 95% CI: 0.74 -0.98, P = 0.02), the number of heart failure exacerbation events (RR = 0.69, 95% CI: 0.50 -0.95, P = 0.02), and the number of rehospitalization events due to heart failure (RR = 0.71, 95% CI: 0.58 -0.86, P < 0.05) in the SGLT2 inhibitors-treatment group compared to a placebo or standard care (control group). SGLT2 inhibitors improved patient quality of life (SMD = -0.24, 95% CI: -0.40 --0.09, P = 0.002). SGLT2 inhibitors were associated with enhanced diuresis in patients with AHF (MD = 2.83, 95% CI: 1.36 -4.29, P < 0.05). Overall, treatment with SGLT2 inhibitors significantly reduced the level of serum NT-proBNP (MD = -497.62, 95% CI: -762.02 --233.21, P < 0.05) and did not increase the incidence of adverse events (RR = 0.91, 95% CI: 0.82 -1.01, P = 0.06).This meta-analysis suggests that treatment with SGLT2 inhibitors is associated with a better prognosis in patients with AHF than in patients not treated with SGLT2 inhibitors. It is safe and effective to initiate SGLT2 inhibitors in patients with AHF.